2018
DOI: 10.3324/haematol.2018.194241
|View full text |Cite
|
Sign up to set email alerts
|

Tspan18 is a novel regulator of the Ca2+ channel Orai1 and von Willebrand factor release in endothelial cells

Abstract: Ca 2+ entry via Orai1 store-operated Ca 2+ channels in the plasma membrane is critical to cell function, and Orai1 loss causes severe immunodeficiency and developmental defects. The tetraspanins are a superfamily of transmembrane proteins that interact with specific ‘partner proteins’ and regulate their trafficking and clustering. The aim of this study was to functionally characterize tetraspanin Tspan18. We show that Tspan18 is expressed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 59 publications
6
27
0
Order By: Relevance
“…In the current absence of an effective Tspan18 antibody, we used RT-PCR to demonstrate Tspan18 expression in human endothelial cells, but not most other cell types. This was supported by our analyses of publicly available RNA-Seq data from mouse lung and brain, which showed that Tspan18 is most highly expressed in endothelial cells of these organs [6]. Analysis of single-cell RNA-Seq data from 20 mouse organs provides further support, since 9 of the 14 most highly Tspan18-expressing cell types are endothelial cells (Fig.…”
Section: Tspan18 Regulates Orai1/ca 2+ Signaling On Endothelial Cellssupporting
confidence: 57%
See 3 more Smart Citations
“…In the current absence of an effective Tspan18 antibody, we used RT-PCR to demonstrate Tspan18 expression in human endothelial cells, but not most other cell types. This was supported by our analyses of publicly available RNA-Seq data from mouse lung and brain, which showed that Tspan18 is most highly expressed in endothelial cells of these organs [6]. Analysis of single-cell RNA-Seq data from 20 mouse organs provides further support, since 9 of the 14 most highly Tspan18-expressing cell types are endothelial cells (Fig.…”
Section: Tspan18 Regulates Orai1/ca 2+ Signaling On Endothelial Cellssupporting
confidence: 57%
“…We further showed that Tspan18 knockdown in primary human umbilical vein endothelial cells (HUVECs) impairs Ca 2+ signaling by 55-70% following stimulation with the GPCR agonists histamine or thrombin, similar to Orai1 knockdown [6]. Orai1 surface localisation is 70% reduced following Tspan18 knockdown, suggesting a role for Tspan18 in trafficking Orai1 from the ER.…”
Section: Tspan18 Regulates Orai1/ca 2+ Signaling On Endothelial Cellsmentioning
confidence: 74%
See 2 more Smart Citations
“…Other recent biomarkers have been or are currently explored for the diagnosis or venous thrombosis and they may be grouped into those with limited or no signal, mixed results or strong results, but they require further validation before considering their use in clinical practice [7,142,143] (Table 4). Although many of these biomarkers are very promising, currently, they cannot be used to make decisions in the management of patients with venous thromboembolism because they do not have an established cut-off point in order to validate them, and most of them have not been used in clinical trials.…”
Section: Other Biomarkersmentioning
confidence: 99%